Asymptotical approximation of one dimensional gas dynamics problem - Krylovas, Aleksandras; Lavcel-Budko, Olga (Lietuvos matematikos rinkinys, 2013)
We analyze nonlinear one dimensional gas dynamics system. The constructed asymptotic approximation which describes periodic acoustics waves resonant interaction is uniformly valid in the long time interval. The results allow to determine the resonance conditions for the emergence and summarizes the previous analyzed polytropic ideal-gas case.
Keywords: gas dynamic; acoustic waves; resonance; asymptotics methods